Post Harvest Studies in Adhatoda. (A.Zeylanica (Medic) & A.beddomei (Clarke)) - Sujatha M P (Department of Processing Technology, College of Horticulture, 2002)
An experiment was conducted in the Department of Processing Technology, College of Horticulture, Vellanikkara during 2001-2002 to evolve a suitable drying regime for adhatoda and to find out the suitable packaging materials ideal to store the dried samples and hot water extracts with minimum quality deterioration. - Sun drying of the whole plant chopped into pieces was evolved as the best drying technique with respect to the quality attributes like vasicine content and alcohol as well as water soluble extracts for A. zeylanica and A. beddomei. Chopping of the whole plant helped in achieving faster drying. Roots of adhatoda also have sufficient quantity of medicinally active constituent vasicine. So uprooting the whole plant would be better than taking aerial cuttings alone. Sundried chopped pieces stored in 250 gauge polyethylene bags and powdered samples in steel containers had maximum retention of principal alkaloid vasicine after storage in room temperature for 5 months for both the species and the same samples also recorded the lowest microbial content whereas for hot water extract, glass bottles were more ideal than plastic bottles as it gave better shelf life, higher retention ofvasicine and lower microbial count. The technique thus developed can help to store the materials in a limited space for longer time without much spoilage or quality deterioration besides three times the quantity of dried whole plant could be accommodated when it is powdered and stored in rigid containers, additionally it adds convenience for the usage.